Essential oil chemotypes of Aloysia citrodora (Verbenaceae) in Northwestern Argentina - Elechosa, Miguel Angel; Di Leo Lira, Paola Maria del Rosario; Juarez, Miguel Angel; Viturro, Carmen Ines; Heit, Cecilia I.; Molina, Ana C.; Martinez, Alejandro; Lopez, Simon; Molina, Ana Maria; van Baren, Catalina María; Bandoni, Arnaldo Luis (Elsevier, 2018)
Chemical biodiversity of essential oils of natural populations of Aloysia citrodora Palau (“lemon verbena”, “cedrón”) in Northwestern Argentina was assessed by collecting in the same sites through different years. A total of 36 samples were collected in the Provinces of Salta (El Maray, La Paya, El Sunchal, El Alisal, Chorrillos), Jujuy (Chilcayo, San Roque), Catamarca (Mutquin, Colana) and Tucumán (Amaicha del Valle) in Argentina. Essential oils were obtained by hydrodistillation (Clevenger) of naturally air-dried plant material. Yields ranged from 0.16% to 1.93% (v/w), being the highest those of the collections of Mutquin. More than 65 compounds were identified by CG-FID-MS. Only 19 of these constituents, accounting from 77.3 to 98.9% of the total oil, present in more than 4.0% in at least one sample, were considered as variables for statistical analysis. Agglomerative Hierarchical Cluster analysis was conducted, showing at 65% of similarity, five groups. This grouping was in direct accordance to the biosynthetic pathways of main compounds (chemotypes). In the two sites of Jujuy, 21 collections evidenced four different chemotypes, named after the dominant component as follows: thujones, citronellal, carvone, and citral (neral + geranial). In the populations of Salta and Catamarca, linalool appeared as a new different chemotype. Though cedron is considered as a citral-bearing plant, curiously, in the 36 samples collected in the NW of Argentina, only two samples contained citral as main constituent. On the other hand, a dominance of citronellal and thujones compositions were found in the bulk of the samples collected, while others had very high content of linalool or carvone and its derivatives. Northwestern Argentina has repeatedly been mentioned as the center of biodiversity of this species. The new evidences found on the chemical biodiversity of essential oils of Aloysia citrodora in natural populations in this region, reinforce firmly this idea.